2021
DOI: 10.1182/bloodadvances.2020004110
|View full text |Cite
|
Sign up to set email alerts
|

Spotlight on eltrombopag in pediatric ITP in China: a long-term observational study in real-world practice

Abstract: Immune thrombocytopenia (ITP) is an autoimmune bleeding disorder with isolated thrombocytopenia and risk of hemorrhage. Treatment with eltrombopag increases and maintains hemostatic platelet counts; however, to date, long-term data are lacking on the outcome of children with ITP who are treated with eltrombopag. This prospective, observational, longitudinal cohort study evaluated the efficacy and safety of eltrombopag in pediatric patients with persistent or chronic ITP. For the 116 pediatric patients enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 23 publications
7
22
0
Order By: Relevance
“…Outside of RCTs, a recent observational cohort study on eltrombopag in paediatric ITP patients reported 77% (89 of 116 patients) responded by meeting the platelet count criteria of ≥30 × 10 9 /L for six or more weeks in the absence of rescue therapy. 10 Similar to the RCTs, there were no significant side effects reported in this study.…”
supporting
confidence: 80%
See 3 more Smart Citations
“…Outside of RCTs, a recent observational cohort study on eltrombopag in paediatric ITP patients reported 77% (89 of 116 patients) responded by meeting the platelet count criteria of ≥30 × 10 9 /L for six or more weeks in the absence of rescue therapy. 10 Similar to the RCTs, there were no significant side effects reported in this study.…”
supporting
confidence: 80%
“…This platelet count response is using the definition of response of platelet count criteria of ≥50 × 10 9 /L for six or more weeks in the absence of rescue therapy. Using a more liberal definition of response—defined as a platelet count ≥30 × 10 9 /L or at least doubling of the baseline platelet count, and absence of bleeding—the response rate (15/20 or 75%) was also similar to a recently published prospective observational cohort 10 …”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…In our center, we treated GT insensitivity patients with an escalating treatment strategy 47 and the long-term treatment with eltrombopag was generally safe, well tolerated, and effective in maintaining platelet counts and reducing the incidence of CITP in most pediatric patients with persistent ITP. 48 So, the specific SNP may not be associated with the development of CITP in this cohort. In addition, SNPs (STAT1, 1 TNFβ, 9 IL-17F, 12,13 SDF1, 10 and FCGRIIb 14 ) associated with development of CITP are different from SNPs (SIRT1, 15 SDF1, 10,16 ABCB1, 17 TNFα, 18 and IL-23R 19 ) associated corticosteroid sensitivity except SDF1.…”
Section: Discussionmentioning
confidence: 77%